NK1.1 Expression Defines a Population of CD4+ Effector T Cells Displaying Th1 and Tfh Cell Properties That Support Early Antibody Production During Plasmodium yoelii Infection - Wikenheiser, Daniel J.; Brown, Susie L.; Lee, Juhyung; Stumhofer, Jason S. (Frontiers in Immunology, 2018)
Early plasmablast induction is a hallmark of Plasmodium infection and is thought to contribute to the control of acute parasite burden. Although long understood to be a T-cell dependent phenomenon, regulation of early plasmablast differentiation, however, is poorly understood. Here, we identify a population of CD4+ T cells that express the innate NK cell marker NK1.1 as an important source of T cell help for early plasmablast and parasite-specific Ab production. Interestingly, NK1.1+ CD4+ T cells arise from conventional, naive NK1.1- CD4+ T cells, and their generation is independent of CD1d but critically reliant on MHC-II. CD4+ T cells that express NK1.1 early after activation produce IFN- and IL-21, and express the follicular helper T (Tfh) cell markers ICOS, PD-1 and CXCR5 more frequently than NK1.1- CD4+ T cells. Further analysis of this population revealed that NK1.1+ Tfh-like cells were more regularly complexed with plasmablasts than NK1.1- Tfh-like cells. Ultimately, depletion of NK1.1+ cells impaired class-switched parasite-specific antibody production during early Plasmodium yoelii infection. Together, these data suggest that expression of NK1.1 defines a population of rapidly expanding effector CD4+ T cells that specifically promote plasmablast induction during Plasmodium infection and represent a subset of T cells whose modulation could promote effective vaccine design.